2017
DOI: 10.1080/20008198.2017.1407202
|View full text |Cite
|
Sign up to set email alerts
|

The role of guilt in Posttraumatic Stress Disorder

Abstract: Background: A growing body of evidence supports the notion that the emotional profile of Posttraumatic Stress Disorder (PTSD) may be more diverse than traditional accounts presume. PTSD’s image as an anxiety-based disorder is undergoing change as the significance of other emotions in its development becomes more evident. Experimental research is needed in order to expand the understanding of underlying processes driving the development of PTSD. Objective: Experimentally test the influence of stressor-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Although fear and guilt may both predict PTSD and PTG, the predictive mechanisms remain unclear. According to Lee et al's (2001) theory of PTSD generation mechanisms and to previous research, we propose that rumination may mediate the effects of fear and guilt on PTSD and PTG (Bub & Lommen, 2017;Dekel et al 2016;. Rumination is a cognitive process consisting of repeated attempts to analyse one's problems and feelings of distress, but with no accompanying action to make positive changes (McEvoy, Watson, Watkins, & Nathan, 2013).…”
Section: The Mediating Role Of Ruminationmentioning
confidence: 78%
See 1 more Smart Citation
“…Although fear and guilt may both predict PTSD and PTG, the predictive mechanisms remain unclear. According to Lee et al's (2001) theory of PTSD generation mechanisms and to previous research, we propose that rumination may mediate the effects of fear and guilt on PTSD and PTG (Bub & Lommen, 2017;Dekel et al 2016;. Rumination is a cognitive process consisting of repeated attempts to analyse one's problems and feelings of distress, but with no accompanying action to make positive changes (McEvoy, Watson, Watkins, & Nathan, 2013).…”
Section: The Mediating Role Of Ruminationmentioning
confidence: 78%
“…A meta-analysis (Pugh, Taylor, & Berry, 2015) of the relationship between guilt and PTSD found that they are strongly related, and that guilt may predict the occurrence of PTSD. Experimental studies have also confirmed that the arousal of guilt can predict symptoms of PTSD (Bub & Lommen, 2017). On the other hand, as a selfconscious emotion, guilt can facilitate psychological adaptation (Tangney & Tracy, 2012), which promotes the adoption of positive coping strategies and the emergence of more altruistic behaviour.…”
Section: Guilt Affects Ptsd and Ptgmentioning
confidence: 99%
“…In a follow-up study, post-film anxiety levels again predicted intrusions ( Laposa & Rector, 2012 ). Feelings of guilt (experimentally manipulated using a staged computer crash and related loss of data) also predicted the number of intrusive memories of the event and intrusion-related distress ( Bub & Lommen, 2017 ).…”
Section: Insights From Cognitive Science On the Development Of Intrusmentioning
confidence: 99%
“…Studies report that guilt experienced in response to traumatic/ stressful event may lead to development of stress disorder. 31 Limitations of the study The present study was performed with small sample size for assessing the effect of stress on judgment, psychological health and adjustment level. The results of the study maybe specific to the type of subject chosen and individual variation in genetic make up to handle stressful situations.…”
Section: Discussionmentioning
confidence: 94%